Neoliberal Values and Traditional Gender Roles: The Construction of Resilience after 3.11 Japan (KULT_online, 2021)
Mire Koikari’s book analyzes cultural production in Japan after the disaster that took place in March 2011. The book proposes a critical look at values, discourses, and practices in constructing a culture of resilience in Japan. Far from being an impartial and uniform practice, Koikari argues that the new impetus for the politics of resilience has also deepened neoliberal values and traditional gender roles.